2011
DOI: 10.1111/j.1741-4520.2011.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melanocortins on fetal development

Abstract: Melanocortins, adrenocorticotropic hormone (ACTH) and α-, β-, and γ-melanocyte-stimulating hormone (MSH) are produced in the placenta and secreted into embryos/fetuses. ACTH concentrations are higher in fetal plasma than in maternal plasma and peak at mid-gestation in rats, whereas ACTH production starts in the anterior lobe of the fetal pituitary at later stages. Melanocortin receptors (MC1-5R), receptors for ACTH and α-, β- and γ-MSH, are expressed in various adult organs. The specific function of these rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 87 publications
(162 reference statements)
0
15
0
Order By: Relevance
“…We have previously shown that one of the pro-inflammatory cytokine belonging to the IL-6 family cytokines, leukemia inhibitory factor (LIF), is required for fetal brain development [ 11 , 12 ]. We also demonstrated that rat maternal LIF induces adrenocorticotropic hormone (ACTH) from the placenta, which in turn stimulates fetal nucleated red blood cells to secrete LIF, leading finally to neurogenesis in the cerebrum of the fetus [ 13 , 14 ]. This maternal—fetal signal relay pathway of maternal LIF–ACTH–fetal LIF via the placenta (maternal–fetal LIF signal relay) was shown in rats at mid-gestational stage [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that one of the pro-inflammatory cytokine belonging to the IL-6 family cytokines, leukemia inhibitory factor (LIF), is required for fetal brain development [ 11 , 12 ]. We also demonstrated that rat maternal LIF induces adrenocorticotropic hormone (ACTH) from the placenta, which in turn stimulates fetal nucleated red blood cells to secrete LIF, leading finally to neurogenesis in the cerebrum of the fetus [ 13 , 14 ]. This maternal—fetal signal relay pathway of maternal LIF–ACTH–fetal LIF via the placenta (maternal–fetal LIF signal relay) was shown in rats at mid-gestational stage [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in melanocyte‐stimulating hormone (α‐MSH) produced by the placenta is one of many physiological and hormonal changes in pregnancy and may have a mechanistic role in ameliorating EPP symptoms. Of note, synthetic α‐MSH is an emerging treatment to increase tolerance to sunlight in EPP …”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that ACTH is important for embryonic differentiation [6]. In the placentas, MC2R (ACTH-R) is known to be high, and a fetal animal is directly affected by ACTH level [7].…”
Section: Discussionmentioning
confidence: 99%